Geochemical markers of human occupation in the lower Argens valley (Fréjus, France): from protohistory to Roman times. (February 2018) - Véron, Alain; Morhange, Christophe; Poirier, André; Angeletti, Bernard; Bertoncello, Frédérique
Abstract: Sediments deposited in the lower Argens valley at Fréjus, a well-known Roman Imperial harbor in northwestern Mediterranean, reveal pollutant metal imprints since the Iron Age. Lead, copper and zinc concentrations in sediments above a facies transition from sand (lower) to silt (upper) at 1820–1946 cal. BP (65–130 cal. CE) are four times higher than in the non-contaminated geochemical background unit at the bottom of the core. These correlated chemical and sedimentological shifts in the ancient marine bay follow the growth of the Augustan city subsequent to the building of the Roman harbor during the late first century BCE. Trace metal enrichment factors (calculated from background concentrations) display a slight but significant increase (1.3 to 1.5) in sediments deposited during the Fréjus protohistoric period, just below the facies transition. This enrichment is corroborated by mean 206 Pb/ 207 Pb isotope ratios that vary from 1.179 (± 0.002) to 1.193 (± 0.002) and 1.202 (± 0.002) in the Roman, protohistoric and background units respectively. These findings are the first evidence of pollutant metal release into the lower Argens ria during the protohistoric period, as far as 2600 years ago. Lead isotope signatures in the protohistoric sediment layers shed light on several possible geographic origins for ores from which accumulated pollutant metals may originate. These include copper mines in the Alps or the Languedoc regions. Cyprus may also be isotopically invoked as a source that is not supported by archaeological findings and would constitute, if proven true, a new insight regarding metal trades in protohistoric Gaul. Highlights: Evidence of heavy metal (Cu, Pb, Zn) enrichments in the Imperial Roman harbor of Fréjus (northwestern Med., France). First geochemical indication of pollutant metal dispersion in the lower Argens valley during the Iron Age. Isotopic markers reveal possible protohistoric metal trades with Alpine and/or Cyprus mining regions. Chemical findings suggest the need for further Iron Age archaeological and paleoenvironmental investigations in Fréjus area.